Towards sustainable microfinance: The case of Capitec Bank and Grameen Bank - Verryn, Annette (Graduate School of Business (GSB), 2019)
This thesis investigates the level of sustainability of two microfinance institutions (MFIs): Grameen Bank of Bangladesh and Capitec Bank of South Africa. Data from 2004 to 2013 is used in this study employing internationally accepted sustainability criteria, namely, the Small Enterprise Education and Promotion (SEEP) 2010 Microfinance Financial Reporting Standards (MFRS) and the SEEP Framework of 2005. The results of this study indicate that although the operations of both microfinance institutions are sustainable, Capitec Bank exhibits a higher level of sustainability as compared to Grameen Bank. This is evidenced by Capitec Bank’s higher levels of profitability, capital adequacy and solvency, operational self-sufficiency, and healthier asset portfolio. This finding underlines South Africa’s financial sector’s stability, institutional quality, competitive market, and solid regulatory framework. The sustainability criteria suggest that Capitec Bank and other South African MFIs should heed Grameen Bank’s low ROE and insufficient capital adequacy and solvency measures. Ensuring healthy and strategic lending portfolios gives a good ROE for a firm’s shareholders. Furthermore, the capital adequacy and solvency ratios have important implications for an institution’s capital structure. Therefore, Capitec and South African MFIs should maintain healthy ROE, capital adequacy and solvency ratios in order to ensure their long-term sustainability. As future research, it would be useful if data were made available to enable an assessment of a failed South African MFI to obtain clearer insight into the South African microfinance sector. Furthermore, data on Grameen and Capitec’s asset quality and social performance will give additional insight into the social sustainability of these two MFIs.